The school - Henao-Hidrón, Javier (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The transcendence that has the place where knowledge is transmitted and developed, main source of human being training, had a great development in ancient civilizations through Europe that serves as example for the formation of a Colombian educational model that was initially characterized by its gratuitousness and compulsory, clearly understood as the basis for development of a state.